Efficiacy of Prostatex Plus in the prevention of prostate biopsy complications - I. A. Aboyan; S. V. Grachev; S. M. Pakus; K. I. Badyan (Вестник урологии)
Introduction. The most frequent complications after fine-needle biopsy of the prostate gland are infections and inflammations, which can occur in up to 17 % of cases. Currently, there is no standardised protocol for preventing infectious complications, including the choice of medication, duration, and timing of administration.   Objective. To evaluate the effectiveness of Prostatex Plus in combination therapy after prostate biopsy compared with the generally accepted approach to patient management.   Materials and methods. A prospective study involved 62 men undergoing examination and treatment at the Regional Clinical and Diagnostic Centre «Zdorovie». Transrectal biopsy was performed using a Philips HD 11 ultrasound scanner with an endfire transrectal probe. All patients were divided into two groups: Group 1 — 30 people who received antibacterial therapy plus Prostatex Plus for 20 days. Patients completed standard urological questionnaires IPSS and NIH-CPSI preoperatively, on day 7 and 30.   Results. Group 1 patients showed worsening of symptoms at 7 and 30 days after biopsy compared to preoperative values according to IPSS. Aggravation of symptoms severity according to the NIH-CPSI questionnaire was observed on the day 7, by the day 30 the worsening of symptoms levelled out. Similar results were obtained when analysing the indicators of group 2: both IPSS and NIH-CPSI questionnaire showed worsening of the patients' condition by the post-op day 7, and on the post-op day 30 it was statistically significantly higher in comparison with the primary indicators (p = 0,001). Patients with a history of abacterial prostatitis showed a difference in IPSS scores 30 days after biopsy (p = 0.020). A similar situation was observed regarding pain syndrome according to the NIH-CPSI.   Conclusion. Patients with abacterial prostatitis who received Prostatex Plus showed statistically significant improvement in the symptomatology of urinary disorders and pain syndrome than patients who received antimicrobial therapy alone.